Control interno contable del efectivo y equivalente del efectivo y su aporte a la razonabilidad de los estados financieros - Leon Tinoco, Dayse Raquel (2015)
The present work of titling, has as a purpose of the diagnostic group of account of the Cash and Cash Equivalents using the tool of internal control to protect and safeguard the company's cash. The methodology aims to achieve a level descriptive research. The types of research that are applied in this work are the field of bibliographic and documentary. Applies the technique of questionnaire and observation that enabled the gathering of information. Being our objective to carry out the diagnosis in the company EXCALNOB S. A, by means of the tool of the group internal control Cash and Cash Equivalents, to implement accounting policies that help to safeguard the cash, and proceeded to strengthen a proper control in this area. By what we have determined that the application of tools for control in the business helps to determine weaknesses and avoid risk that lead to the economic instability of the same. Recommending to the Administrator or manager who meets in the implementation of controls, which allow it to generate reasonably the financial statements of the company, as well as other reports relevant to the control and operation of the body.